Uma experiência de ensino da geometria plana de polígonos para alunos com deficiências visuais. - DIAS, Leonardo José dos Passos (2024)
This course completion work intends to overcome the teachers’ difficulties in passing on the knowledge of Plane Geometry to blind and low vision students. Using concrete materials, such as a clipboard, slate and punch, and other materials, such as the Multiplane kit, for a “better” reception of the visually impaired. For a more playful and relaxed way of the main mathematical concepts, through touch, with angles, straight lines, segments and other "palpable"mathematical objects, in view of these students’ access to the mathematical universe.